Development directions of microregional spatial environments - Varga, Ferenc; Sinóros-Szabó, Botond; Köpeczi-Bócz, Tamás (Acta Agraria Debreceniensis, 2014)
The question how economic, technological and infrastructural developments, as well as products and technologies contribute to the unity and constant strengthening of the society is still unanswered both in Europe and the whole world.The current erosion of the society and the weakening social cohesion is a regrettable process. These phenomena are a barrier to real development processes and weaken the extension of the economic space; therefore, this negative process has to be stopped and turned into a positive direction.For this reason, it is increasingly urgent to work out new, feasible solutions, since it has become obvious that solutions whose sole aim is to increase profit typically weaken the indispensable unity of the society, market positions, innovation processes, as well as natural and environmental harmony.In this situation, we analysed and interpreted the disadvantaged and multiply disadvantaged microregional spatial environments, with special regard to the strategic developments that serve both the strengthening of the microsocieties of microregional spaces and the development of the economy and the extension of economic space.The identification of disadvantaged microregional spaces is basically done by means of economic indexes, but it is also important to emphasise that these indexes can only be interpreted with social indexes, as they define the situation of the microregional space and the possible development directions together.The constant strengthening of social unity (cohesion) and the related economic development is basically a new focal point and objective.